Dark tourism in Malaysia: a growing sector? / Muhammad Hanif Othman and Zouhair Mohd Rosli - Othman, Muhammad Hanif; Mohd Rosli, Zouhair (Universiti Teknologi MARA, Kedah, 2023)
Tourism is a vital engine for socioeconomic development, contributing significantly to the host country's value-added and employment. The expansion of the tourism industry will have a favorable impact on closely associated service industries, such as entertainment, food and beverage accommodation, transportation, shopping, and small and medium-sized companies (SMEs). The labor-intensive nature of the tourism industry will produce job opportunities and cash for the local communities. The expansion of the tourism industry in Malaysia would not only provide numerous economic advantages – through its direct, indirect, and induced effects – in the form of money, production, and job possibilities, but it would also enhance the country's long-standing cultural variety (Mohd Rosli, 2014). The innovation of tourism products and services is crucial for increasing the amount of spending by both domestic and international visitors, the duration of stay in the host country, as well as the number of tourists in Malaysia. Therefore, under the Shared Prosperity Vision (SPV) 2030, the tourism sector is listed under the Key Economic Growth Area (KEGA) under the themes of ASEAN Hub, Coastal and Maritime Economies, and Malaysia Truly Asia, respectively (Ministry of Economic Affairs, 2019). Almost all states in Malaysia are tasked with pushing the tourism development agenda further in the next decade, namely: Perlis (Ecotourism); Penang (Health and heritage tourism); Perak (Ecotourism and heritage tourism); Kuala Lumpur (ASIA gateway); Malacca (Ecotourism and heritage tourism); Negeri Sembilan (Ecotourism and heritage tourism); Kedah (Ecotourism and heritage tourism); Johor (Ecotourism and heritage tourism); Pahang (Ecotourism); Sarawak (Ecotourism); Sabah (Ecotourism); Kelantan (Heritage tourism, ecotourism, and agrotourism); and Terengganu (Island and coastal tourism). Furthermore, new specialty products have been created and marketed. Culture-based tourism, community-based tourism, ecotourism, agrotourism, natural attractions (wildlife sanctuaries, national parks, highlands, and islands), heritage tourism, and dark tourism are examples of emerging niche products that continue to draw large tourism demand (Mohd Zahari et al., 2016; Mohd Rosli, 2014; Hanafiah & Hemdi, 2014). Dark tourism, also known as thanatourism, is traveling to locations linked with death, sorrow, and suffering, such as war monuments, disaster zones, and concentration camps (Rojek, 2003). In recent years, there has been a rising interest in dark tourism as a sort of cultural and historical tourism, and a number of nations are establishing these types of places as destination brands (Stone, 2006). Malaysia is not an exception, and the country's development of dark tourism as a destination brand has the potential to contribute to the preservation of significant cultural and historical landmarks and provide tourists with a meaningful and informative experience. The Malaysian government has promoted Malaysia's dark tourism as one of the country's possible sources of revenue (Dorcheh & Mohamed, 2013). The preservation of these places in Malaysia could attract international as well as domestic tourists to come to Malaysia (Economic Planning Unit, 2006; Bhuiyan et al., 2013). Some of the potential dark tourism products in Malaysia are Jerejak Island in Penang, the Penang War Museum, Pulau Bidong in Terengganu, The Second World War Sandakan – Ranau Death March, Mahsuri in Langkawi, Taiping Prison, Pudu Jail at the city center of Kuala Lumpur, and the magnificent Kellie’s Castle in Perak (Mohd Zahari et al., 2016; Masanti, 2016; Tan & Lim, 2018). These dark tourism attractions can draw a substantial number of people, both international and domestic, and therefore can increase tourism revenue. In addition, the reasons that contribute to the acceptability of dark tourism in Malaysia, such as its historical and cultural value, educational 60 possibilities, and economic impact on local communities by creating employment and increasing tourism earnings.